Emulating Sayyidah Fāṭimah al-Zahrāʾ in Classical and Contemporary Literature for Moral Education Transformation - Masruroh Masruroh; A. Syathori (Bulletin of Indonesian Islamic Studies, 2025)
This study examines the moral exemplarity of Sayyidah Fāṭimah al-Zahrāʾ through a systematic review of classical Islamic literature and contemporary scholarship as a foundation for transforming moral education among Muslim women. In the digital era—marked by ethical crises—Fāṭimah al-Zahrāʾ is positioned as an ideal figure representing core Islamic values that are both contextually relevant and applicable to character formation, including ethical technology use and civil digital interaction. Adopting a normative orientation, the study applies a thematic approach in reviewing both classical Islamic texts and modern academic sources. The analysis identifies three central themes: (1) Fāṭimah’s personal and spiritual virtues, such as honesty, patience, and devotion; (2) her role in family education as a moral exemplar; and (3) the actualization of her values in digital spaces through ethical communication and moral responsibility. The study concludes that Fāṭimah al-Zahrāʾ’s character offers a practical and context-sensitive model for moral learning, especially within Islamic educational settings such as pesantren. These findings provide both conceptual and practical contributions to the development of value-based curricula and character education modules rooted in Islamic ethics that are responsive to contemporary challenges.